(untitled) (The Review of Diabetic Studies, 2025)
The protein’s isolation and purification were part of this thesis. protein from serum in the blood of an individual with gluacoma disease, the investigation of various elements influencing its efficacy, along with figuring out its molecular weight. In which Ammonium sulfate deposition produced a protein leachate, which was treated with the DEAD-Cellulose ion exchanger. (0-65%) following dialysis membrane sorting.The enzyme’s high efficacy was demonstrated by the package, which was also used to determine the enzyme’s molecular weight using SDS-PAGE and electrical migration technology, which was roughly equivalent to 66,000 kilodalton. As for the concentration of the protein, the findings indicated that an increased protein concentration would result in an increase in enzyme activity.